Kesadaran Metakognitif Siswa dalam Pembelajaran Berbasis Proyek pada Pokok Bahasan Pencemaran Lingkungan - Adhitama, Rizky Sandy; Kusnadi, Kusnadi; Supriatno, Bambang (Assimilation: Indonesian Journal of Biology Education, 2018)
The purposes of this research are to investigate the level of senior high school student’s metacognitive awareness, the relationship between knowledge about cognition and regulation of cognition, and the relation among all indicators of metacognitive awareness which examined through project-based learning in Environtmental Polution concept. The subject of this study is first grade-students in one of public high school in Bandung. To reveal metacognitive awareness, we used Metacognitive Awareness Inventory modified from Schraw and Dennison (1994). The results of this research revealed that majority of students have good metacognitive awareness level, and the rest are very good and adequate. Then, majority of students have good level of knowledge about cognition and regulation of cognition aspect. The results also revealed that there are very high correlation between knowledge about cognition and regulation of cognition. Metacognitive awareness indicators have also high correlation among them, except declarative and procedural knowledge, which have a low correlation. Through this research, we found that project-based learning are able to facilitated the students to use their metacognitive awareness in Environtmental Polution concepts with the learning process.